The decline of relational goods in the production of well-being? - Aloys Prinz; Björn Bünger (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2009)
In this paper, we attempt to show why the importance of relational goods compared to conventional goods and status goods threatens to decline in contemporary societies. In our point of view, the development of the relative significance of these three types of goods is not a consequence of preference changes but of significant alterations in the opportunity costs of time. Increases of labor productivity in the industrial sector lead to higher time opportunity costs that reduce the demand for highly time-consuming activities as relational goods. Furthermore, the demand for status goods may increase in societies that grow rich as these goods can be bought to a large extent on the market and serve physical as well as psycho-social well-being. As shown empirically, there exist influences of the availability of free time on meeting friends and on life satisfaction. However, for the European countries represented in the dataset, we cannot find evidence yet for a crowding out of relational goods by status goods.
Keywords: D11; D60; I31; 330; conventional; relational and status goods; time opportunity costs; production of wellbeing; life satisfaction